Implementação de modelos para o cálculo do ponto de operação de poços de petróleo e seleção do melhor método de elevação artificial - Rodrigues, Igor Adriano de Carvalho (Universidade Federal do Amazonas, 2018)
The impact of each of the integrant of a production system can be analyzed through nodal analysis, which is a very important tool in the design of a well. Currently there are several commercial programs available on the market, based on fluid flow, being widely used in the industry not only to correctly dimension the production column and surface equipment, but also to find the best operating point for well production. However, there is still a shortage of efficient tools of low commercial or free value, for educational purposes in universities. In addition, there is still a very recurrent doubt in production development projects, which is the definition of the method of elevation most appropriate to certain conditions. At this stage, a wrong choice can lead to higher operating costs and reduced revenues due to inefficiency due to a high frequency of failures. On the other hand, in order to choose the best lifting method, it is important to identify the main influence factors. Expert systems are able to select the best method to be used based on human knowledge previously stored in computerized systems, these systems are among the criteria used to make the choice computationally. The objective of the present work is to develop a didactic support tool implementing several mathematical models to obtain Inflow Performance Relationship (IPR) curves and then find the equilibrium point of the well, taking the TPR as an input data, if in the boolean and fuzzy logic, choose the most appropriate elevation method if the well is not in the works, through spreadsheets and Visual Basic for Applications (VBA) of the platform Microsoft Excel, a program widely distributed in most Brazilian universities. The tool includes information on the operational capacity of each lifting method which, when compared to certain input parameters, indicates which method would be most appropriate. And the results concerning the equilibrium point can be analyzed, modified and compared graphically.